Recombinant human erythropoiesis-stimulating agents and mortality in patients with cancer: a meta-analysis of randomised trials. - Bohlius, J; Schmidlin, K; Brillant, C; Schwarzer, G; Trelle, S; Seidenfeld, J; Zwahlen, M; Clarke, M; Weingart, O; Kluge, S; Piper, M; Rades, D; et al. (2009)
BACKGROUND: Erythropoiesis-stimulating agents reduce anaemia in patients with cancer and could improve their quality of life, but these drugs might increase mortality. We therefore did a meta-analysis of randomised controlled trials in which these drugs plus red blood cell transfusions were compared with transfusion alone for prophylaxis or treatment of anaemia in patients with cancer. METHODS: Data for patients treated with epoetin alfa, epoetin beta, or darbepoetin alfa were obtained and analysed by independent statisticians using fixed-effects and random-effects meta-analysis. Analyses were by intention to treat. Primary endpoints were mortality during the active study period and overall survival during the longest available follow-up, irrespective of anticancer treatment, and in patients given chemotherapy. Tests for interactions were used to identify differences in effects of erythropoiesis-stimulating agents on mortality across prespecified subgroups. FINDINGS: Data from a total of 13 933 patients with cancer in 53 trials were analysed. 1530 patients died during the active study period and 4993 overall. Erythropoiesis-stimulating agents increased mortality during the active study period (combined hazard ratio [cHR] 1.17, 95% CI 1.06-1.30) and worsened overall survival (1.06, 1.00-1.12), with little heterogeneity between trials (I(2) 0%, p=0.87 for mortality during the active study period, and I(2) 7.1%, p=0.33 for overall survival). 10 441 patients on chemotherapy were enrolled in 38 trials. The cHR for mortality during the active study period was 1.10 (0.98-1.24), and 1.04 (0.97-1.11) for overall survival. There was little evidence for a difference between trials of patients given different anticancer treatments (p for interaction=0.42). INTERPRETATION: Treatment with erythropoiesis-stimulating agents in patients with cancer increased mortality during active study periods and worsened overall survival. The increased risk of death associated with treatment with these drugs should be balanced against their benefits. FUNDING: German Federal Ministry of Education and Research, Medical Faculty of University of Cologne, and Oncosuisse (Switzerland).